Formation of high-molecular-weight compounds via the heterogeneous reactions of gaseous C8–C10 n-aldehydes in the presence of atmospheric aerosol components. (February 2016) - Han, Yuemei; Kawamura, Kimitaka; Chen, Qingcai; Mochida, Michihiro
Abstract: A laboratory study on the heterogeneous reactions of straight-chain aldehydes was performed by exposing n-octanal, nonanal, and decanal vapors to ambient aerosol particles. The aerosol and blank filters were extracted using methanol. The extracts were nebulized and the resulting compositions were examined using a high-resolution time-of-flight aerosol mass spectrometer. The mass spectral analysis showed that the exposures of the aldehydes to aerosol samples increased the peak intensities in the high mass range. The peaks in the organic mass spectra of the aerosol samples after exposure to different aldehydes were characterized by a homologous series of peak shifts due to the addition of multiple CH2 units. This result is explained by the formation of high-molecular-weight (HMW) compounds that contain single or multiple aldehyde moieties. The HMW fragment peaks for the blank filters exposed to n-aldehydes were relatively weak, indicating an important contribution from the ambient aerosol components to the formation of the HMW compounds. Among the factors affecting the overall interaction of aldehydes with atmospheric aerosol components, gas phase diffusion possibly limited the reactions under the studied conditions; therefore, their occurrence to a similar degree in the atmosphere is not ruled out, at least for the reactions involving n-nonanal and decanal. The major formation pathways for the observed HMW products may be the self-reactions of n-aldehydes mediated by atmospheric aerosol components and the reactions of n-aldehydes with organic aerosol components. The observed formation of HMW compounds encourages further investigations into their effects on the aerosol properties as well as the organic aerosol mass in the atmosphere. Highlights: High-molecular-weight compounds were formed in the presence of atmospheric aerosols. Self-reactions of n-aldehydes are possibly mediated by atmospheric organic components. Reactions of n-aldehydes with atmospheric organic species are another possible pathway.